Konsep Dilālah Fi'li al-Nabi dan Implikasinya Perspektif Fikih Ikhtilaf - Irsyad Rafi; La Ode Ismail Ahmad; Fatimah Fatimah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
This study aim to investigate the concept of dilālah fi'li al-Nabi in terms of interpreting the sunnah from the prophet. This study also aim to know the implication of dilālah fi'li al-Nabi of the perspective of fiqh ikhtilaf. The methodological approach of the study was qualitative literature review using philosophical normative approach and the rules of ushul fiqh approach. The results of this study indicate that: (1) The law of Istinbāṭ sunnah fiʻliyah has been considered to be different from sunnah qauliyah, particularly in an attempt to understand the dilālah. If the sunnah qauliyah is merely interpreted based just only by its language, the fi'liyah sunnah is interpreted based on the essence of prophets’ actions also. Therefore, it is necessary to have a deep understanding of determining the law of the Prophet's actions. The Prophet's position as a qudwah and a human being that Allah has given distinction to him made the application of the law become different to his followers. So that it has to be taken into consideration before deciding any laws related to the prophet’s hadiths. (2) Ikhtilaf uṣūliyīn on dilālah fi'l al-Nabī has implications on various fiqh problems which postulate the actions of the Prophet. Ikhtilaf happens in an attempt to understand fi’l al-Nabī al-mujarrad because there are no supporting argument or the qarīnah, the explanatory instructions which is useful as a lawmaker. Some uṣūliyīn think that taʼassī in terms of the actions done by Nabi Muhammads’ followers will be rewarded by Allah though the actions are not related to any worship. Therefore, the spirit of taʼassī to sunna Nabi must be follewed by a proper understanding and a proper application, because a contradictive application of maqāṣid syarīʻah can happen if it is partially understood and jumūd. In contrast, the other groups that are against this spirit must beware of falling into excessive attitudes that can ruin the good relation between muslims, and must beware of falling into deviations.